Enhanced Ciprofloxacin Ozonation Degradation by an Aqueous Zn-Cu-Ni Composite Silicate: Degradation Performance and Surface Mechanism - Yue Liu; Rong Guo; Jie Li; Yizhen Cheng; Congmin Wang; Weiqiang Wang; Huifan Zheng (Separations)
This study investigates the environmental significance of ciprofloxacin as an emerging contaminant and the need for effective degradation methods. The chemical coprecipitation method was used in this study to prepare the Zn-Cu-Ni composite silicate, serving as a heterogeneous ozonation catalyst. The catalytic activity was then evaluated by degrading ciprofloxacin (CIP). Scanning electron microscopy, X-ray diffraction, X-ray photoelectron spectroscopy, nitrogen adsorption–desorption, and Fourier transform infrared analysis (FTIR) were used to characterize the Zn-Cu-Ni composite silicate. The catalyst had a high surface area (308.137 m2/g), no regular morphology, and a particle size of 7.6 µm and contained Si-O-Si, Ni-O-Si, and Zn-O-Si. The results showed that the CIP degradation and mineralization rates (pH 7.0, CIP 3.0 mg/L, Ozone 1.5 mg/L) were significantly enhanced in the presence of the Zn-Cu-Ni composite silicate. The CIP and total organic carbon (TOC) removal rates were increased by 51.09% and 18.72%, respectively, under optimal conditions, compared with ozonation alone. The adsorption of Zn-Cu-Ni composite silicate, ozone oxidation, and ·OH oxidation synergistically promoted the efficient removal of CIP. This study provides valuable catalytic ozone technology for degradation of antibiotics in wastewater to reduce environmental pollution with potential practical applications.